Maternal Diet and Morbidity Factors Associated with Low Birth Weight in Haiti: A Case?Control Study - Abdirahim Rashid; Thomas Park; Kenneth Macneal; Lora Iannotti; Will Ross (Mary Ann Liebert, 2018)
Objective: A matched, case?control study was conducted to examine the association between development of low birth weight (LBW) and maternal factors, including dietary intake, comorbidities, and socioeconomic factors, among women in Cap Haitien, Haiti. Design: Mothers who delivered LBW babies; defined as ?2.5?kg, were identified by review of the medical record and matched to mothers of similar age, parity, with normal birth weight (NBW) babies. A survey was administered consisting of Women's Dietary Diversity Score (WDDS), maternal reporting of comorbidities, income, and educational level. Subjects: Women were eligible if they delivered and had newborns weighed within the last 2 years. Total study participants consisted of 32 cases and 34 controls matched for age, parity, and month of delivery. Results: Mothers who consume eggs were 78% less likely to have given birth to a LBW infant (OR 0.22 (95% CI: 0.05?0.87). Mothers with NBW babies had a nonsignificant trend towards higher WDDS. The prevalence of hypertension in mothers who were seen in the clinic at least once over the past 2 years was found to be 27%, and 78% of mothers were not aware of their diagnosis. Conclusion: Enhancing maternal nutrition during pregnancy has broad implications for reducing LBW, improving fetal health and reducing fetal predilection for chronic diseases in adulthood. Longitudinal prospective studies are needed to evaluate the selective benefit of eggs and other high-quality foods in protecting fetal growth. Efforts to improve knowledge and awareness of hypertension in Haiti should be undertaken.